Analisis Pola Partnership Dalam Pengelolaan Agrowisata Pagilaran Kabupaten Batang - Muhamad Hilmy Romadhoni; Wiwik Widayati; Lusia Astrika (Journal of Politic and Government Studies, 2015)
ABSTRACTCooperation in the management of Pagilaran tourism is an implementation of Constitution of the Republic of Indonesia Number 32 of 2004 regarding regional autonomy. This law requires local governments to organize and manage the potential that exists in the region. One of the potential tourism that Batang regency has is Pagilaran. Besides that, the purpose of such cooperation is to realize good governance in Batang.This study was conducted to describe the patterns of cooperation in managing Pagilaran between PT Pagilaran and the Department of Culture and Tourism in Batang Regency. It also explains about the difficulties in such cooperation. This study used qualitative research methods. Data triangulation technique is also used to obtain more accurate data validity. Sources of primary data obtained through interviews with relevant informants and secondary data obtained from documents, records, internet, and other sources which are related to this research. This study was conducted in Pagilaran Tourism Object.Results of this study illustrate a pattern of cooperation in managing Pagilaran. The patterns of cooperation not only done by the government and private sector but also community had. Community was given a role to managing Pagilaran. Community had opportunity to participate in managing Pagilaran which is helping the government to achieve a good governance in Batang Regency and in this case, community participate in public services in the tourism sector. Good cooperation indicators was taken from the efficiency and quality, organization dynamics, effectiveness, and also share risks and benefits. In this study, three of the four indicators which are the efficiency and quality, organizational dynamics, share risks and benefits have been implemented properly. The effectiveness indicator has not done well yet because the government has not implement the obligation yet to take care the facilities that have been agreed in advance. In addition, results also explain the difficulties that exist in this cooperation.Recommendation can be given for stakeholders to coordinate better so that the management of Pagilaran can evolve in the future. Also expected to everyparty to comply the obligations which have been agreed by both parties in advance.Keywords: Regional Autonomy, Cooperation, Good Governance, Tourism